1995
DOI: 10.1515/cclm.1995.33.4.225
|View full text |Cite
|
Sign up to set email alerts
|

Haemostasis Activation Markers in Plasma of Patients with Benign and Malignant Gynaecological Tumours: A Pilot Study

Abstract: Summary: Coagulation and fibrinolysis activation have been investigated in fifty-eight women with recently detected gynaecological tumours. Twenty-six were benign and 32 malignant: of the last group nine patients had metastases. A control group consisted of 31 age-matched healthy women. Prothrombin fragment 1 + 2, thrombinantithrombin III and D-dimer were measured. The median values of all analytes were significantly higher in the malignant tumour group, but not in the benign tumour group, as compared to the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1996
1996
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Interestingly, we observed increasing coagulation activation along with more widespread cancer disease, since patients with localised cancer had elevated plasma levels of F1+2 and TAT solely, while patients with advanced cancer had elevated SF levels in addition. In uterine cancer, similar observations of elevated plasma levels of F1+2 along with localised disease and elevated levels of also TAT and D-dimer along with advanced disease have been reported (25). In a study of patients with melanoma, patients with localised disease had higher plasma levels of F1+2 and TAT than those with benign naevi, and patients with metastatic melanoma had higher levels of D-dimer, too (26).…”
Section: Discussionsupporting
confidence: 63%
“…Interestingly, we observed increasing coagulation activation along with more widespread cancer disease, since patients with localised cancer had elevated plasma levels of F1+2 and TAT solely, while patients with advanced cancer had elevated SF levels in addition. In uterine cancer, similar observations of elevated plasma levels of F1+2 along with localised disease and elevated levels of also TAT and D-dimer along with advanced disease have been reported (25). In a study of patients with melanoma, patients with localised disease had higher plasma levels of F1+2 and TAT than those with benign naevi, and patients with metastatic melanoma had higher levels of D-dimer, too (26).…”
Section: Discussionsupporting
confidence: 63%
“…The binding of the two molecules leads to an inactive complex; the thrombin-antithrombin (TAT) complex. TAT levels ap pear to be one of the most informative parameters in order to discover the alteration of haemostasis especially in lung cancer [3], In previous studies we found that plas ma levels of TAT complexes were higher in neoplastic patients than in a healthy population [4,5], Particularly their values seem to correlate with the stage of the disease, as observed by Rocha et al [6] and Lindahl et al [7] in patients with various malignant diseases [6,7] and by Van Wersch et al [8] in patients with gynecological tumours. Recently, TAT complexes were found to be higher also in those suffering from advanced pulmonary carcinoma as compared with patients with limited disease [9].…”
Section: Introductionmentioning
confidence: 51%